If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(12) + 5y = 20 Multiply 3 * 12 36 + 5y = 20 Solving 36 + 5y = 20 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 5y = 20 + -36 Combine like terms: 36 + -36 = 0 0 + 5y = 20 + -36 5y = 20 + -36 Combine like terms: 20 + -36 = -16 5y = -16 Divide each side by '5'. y = -3.2 Simplifying y = -3.2
| -3x-5=-4 | | 3x-2=x+3 | | -5x-8=-4 | | 10x-158=3x-11 | | y(x-1)-4(x-1)= | | 7[m+9]=-2[m-5]+2 | | 3(5x+11)=-42 | | 3(x+2)-2x+4=x+5 | | (8x-18)+(7x-31)=(13x-9)+(19x-6) | | 12z-9-10z+3-8=z-9+3z+10-10z | | 8x+2x-3x-2x= | | 8x+1=23 | | 5m-10n=2 | | 3a+6b+3c= | | 8x=10+x | | -n-2u=5-n | | 9x+14=-40 | | 15x-3y=-18 | | n/7=12/42 | | -5X-7Y=-70solvey | | (x+2)(x+3)=(x+7)(x-4) | | -5X-7y=-70 | | 3(t+2)+4(t-1)=72 | | 16+6z=-8 | | 3log^7x=9 | | -25y^2-60y+60= | | d/33 | | -109/3 | | F(x)=4x^2-24x+20 | | t/4-7=16 | | 6x+7=-48-5x | | x^2-2.8x=9 |